Zab chos Rig [Variation symbol]dzin srog sgrub kyi rtsa gsum las byȧn bskȧn gso bcas bltas chog tu bkod pa bde chen padma drwa baʼi lam ʼbyed ces bya ba bźugs so - U-rgyan-kun-bzaṅ-bstan-ʼdzin-rdo-rje (s.n., 1978)
Rituals for the invocation and propitiation of the deities of Rig ʼdzin srog sgrub, terma cycle of teaching of the Nyingmapa sect in Tibetan Buddhism.